منهج تعليمي تدريبي وفقا لمديات انصاف الاقطار ومتغيرات الانطلاق الميكانيكية وأثره في تطوير القدرة الانفجارية والانجاز لرماة المطرقة الطلاب - باقر, افتخار مطر; دهش, عادل محمد (Sulaimani Journal for Humanities, 2018)
Summary Introduction and problem of research:- The effectiveness of overthrowing the hammer from the activities of high-intensity and dangerous and dangerous and is one of the four throwing activities, which need to master the skill to learn the main movements accurately and improve some of the important physical abilities in the performance of students because the mass of the tool is not under control as the other effectiveness of throwing the presence of the wire Steel and moving, which separates the hand of the thrower and the iron block, so when the student loses one of these capabilities may be limited in control, which leads to the failure to perform effectively. The importance of research in the use of a training curriculum to use it to increase the student's ability to achieve the optimal technical performance of the movement of throwing and increasing achievement . As for the problem of the research, the researchers are able to reach them because they are the teachers of the field and the field in the Faculty of Physical Education and Sports Science, which is the inability of the student to master the skill of throwing the hammer in a manner that meets the ambition of the teacher and the student. This leads to weak achievement achieved which affects the result on the degree granted to the student. The goal of the research was: 1- Develop a curriculum to be used for training in the learning process as well as in improving the variables of mechanical departure and development of explosive capacity and achievement of students. 2- To recognize the impact of the training program on the explosive ability and digital achievement of students of the second stage College of Physical Education and Sports Sciences. The research hypotheses were. 1- The educational training program positively affects some explosive ability and digital achievement in the ouster of the hammer in the students of the second stage Faculty of Physical Education. The researchers used the experimental approach of the two equal groups. The research society of the second stage students in the Faculty of Physical Education and Mathematical Sciences / University of Kufa (70) students and studied the effect on a sample of (40) students randomly selected. The researchers used the statistical methods (the arithmetic mean, the standard deviation, the T test for the interrelated samples, the T test for the samples) Independent, torsion coefficient). In the fourth section, the researchers dealt with the presentation, analysis and discussion of the results obtained from the main experiment. The researchers came out with several conclusions and recommendations from the study and the most important. 1- The educational curriculum training applied to the experimental group gave positive results in improving explosive power. 2- Students can learn to remove the hammer in this way gives them confidence to perform correctly and overcome the difficulty. The most important recommendations were. 1- The necessity of benefiting from the educational curricula in the teaching process in faculties of physical education and sports sciences that serve the general purpose. 2- It is possible to use the educational curriculum of the students studied by the teachers of the field and field